Latent class analysis identifies functional decline with Amsterdam IADL in preclinical Alzheimer's disease. Issue 1 (1st January 2019) - Villeneuve, Sarah‐Christine; Houot, Marion; Cacciamani, Federica; Verrijp, Merike; Dubois, Bruno; Sikkes, Sietske; Epelbaum, Stéphane; ,; Bakardjian, Hovagim; Benali, Habib; Bertin, Hugo; LaurieBoukadida, Joel Bonheur; et al.
Abstract: Introduction: Trials in Alzheimer's disease (AD) now include participants at the earliest stages to prevent further decline. However, the lack of tools sensitive to subtle functional changes in early‐stage AD hinders the development of new therapies as it is difficult to prove their clinical relevance. Methods: We assessed functional changes over three years in 289 elderly memory complainers from the Investigation of Alzheimer's Predictors in subjective memory complainers cohort using the Amsterdam Instrumental‐Activities‐of‐Daily‐Living questionnaire (A‐IADL‐Q). Results: No overall functional decline related to AD imaging markers was evidenced. However, five distinct classes of A‐IADL‐Q trajectories were identified. The largest class (212 [73.4%]) had stable A‐IADL‐Q scores over 3 years. A second group (23 [8.0%]) showed a persistent functional decline, higher amyloid load ( P = .0005), and lower education ( P = .0392). Discussion: The A‐IADL‐Q identified a subtle functional decline in asymptomatic at‐risk AD individuals. This could have important implications in the field of early intervention in AD.